Penguatan Kader Kelompok Air Dan Aplikasi Hasil Riset Pengolahan Air Untuk Meningkatkan Kesehatan Masyarakat - hamzani, sulaiman; Syarifudin A; Tien Zubaidah (Jurnal Rakat Sehat : Pengabdian Kepada Masyarakat, 2024)
Telok Selong Ulu Village and Telok Selong Village are included in the West Martapura District, Banjar Regency, around 50% of residents live on the banks of the Martapura River, they rely on river water for bathing, washing and toileting (MCK). Every year these two villages are often affected by quite severe flooding, the river water looks very murky and brown. River water can no longer be consumed as before and the community’s life is still classified as lower middle class, as informed by the village head. They hope that there will be support from the government or other parties who can help overcome clean water problems, especially during floods which actually cause a clean water crisis. The aim of this community service activity is that community groups are able to process clean water that meets health requirements. The solution offered is to train cadres of working groups that have been formed and apply the results of research on processing river water into clean water. The target indicator for the achievement of community service activities is the formation of a water processing working group in village communities that is skilled and efficient (able to process clean water and prepare the equipment). Apart from that, it is hoped that it will act as a trigger for the academic community to continue to take action in order to improve the level of public health, especially on river banks. Water processing group cadres are expected to always practice their abilities in water processing using DSRF-USRF reactors for daily water supply that meets health requirements. Apart from that, it is hoped that it can share information with local residents who are experiencing difficulties in providing clean water.